2015
DOI: 10.1111/1462-2920.12725
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic colonization and biocontrol performance of Pseudomonas fluorescensPICF7 in olive (Olea europaea L.) are determined neither by pyoverdine production nor swimming motility

Abstract: Pseudomonas fluorescens PICF7 is an indigenous inhabitant of olive (Olea europaea L.) rhizosphere, able to display endophytic lifestyle in roots, to induce a wide range of defence responses upon colonization of this organ and to exert effective biological control against Verticillium wilt of olive (VWO) (Verticillium dahliae). We aimed to evaluate the involvement of specific PICF7 phenotypes in olive root colonization and VWO biocontrol effectiveness by generating mutants impaired in swimming motility (fliI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 83 publications
(127 reference statements)
2
45
0
1
Order By: Relevance
“…The in vitro production of siderophores was shown for a number of BCAs with antagonistic effect on Verticillium (Berg et al, 1996, 2000; Mercado-Blanco et al, 2004; Li et al, 2010; Xue et al, 2013). However, Maldonado-González et al (2015a,b) showed that siderophore production is not required for biological control of Verticillium wilt by Pseudomonas fluorescens PICF7.…”
Section: Biological Control Of Verticillium Wiltmentioning
confidence: 99%
“…The in vitro production of siderophores was shown for a number of BCAs with antagonistic effect on Verticillium (Berg et al, 1996, 2000; Mercado-Blanco et al, 2004; Li et al, 2010; Xue et al, 2013). However, Maldonado-González et al (2015a,b) showed that siderophore production is not required for biological control of Verticillium wilt by Pseudomonas fluorescens PICF7.…”
Section: Biological Control Of Verticillium Wiltmentioning
confidence: 99%
“…Moreover, bacterial antagonists of olive phytopathogens isolated from the olive root endosphere or the rhizosphere have the advantage to be adapted to the ecological niche where they can potentially exert their beneficial effect 18 . For instance, Proteobacteria and Firmicutes representatives, usually found as natural inhabitants from the olive rhizosphere, are thus good examples of effective antagonists against V. dahliae 16–18,29 . Besides, representatives of these phyla such as the genera Pseudomonas and Bacillus are easy to isolate, manipulate, propagate and formulate as BCAs.…”
Section: Discussionmentioning
confidence: 99%
“…Czaban et al (2007) conferred that the flagellar motility is an important feature in the bacterial colonization (especially the root interiors) based on the observation that revealed greater proportion of motile strains in endosphere than the rhizoplane and rhizosphere. However, Maldonado-González et al (2015) observed that there was no difference in endophytic colonization of P. fluorescens PICF7 in olive on mutation in flil gene required for the swimming motility. This observation indicates different mode of colonization required by various endophytes.…”
Section: Chemotactic Migration Towards Rootsmentioning
confidence: 91%
“…However, it is exclusively strain dependent as the O-antigenic side chain of P. fluorescens WCS374 does help in potato root adhesion, whereas the chemical components of O-antigen chain of P. fluorescens PCL1205 contributed in tomato root colonization (Berendsen et al 2015). However, Maldonado-González et al (2015) conducted a ground breaking study to investigate the role of swimming motility, siderophore pyoverdine production, cysteine auxotrophy on olive root colonization and biocontrol activity of P. fluorescence PICF7. It is an indigenous strain that colonizes root tissues of olive and imparts effective biocontrol against Verticilium dahliae, a causative agent of verticilium wilt in olive.…”
Section: Quorum Sensing: Cell Density Dependent Colonizationmentioning
confidence: 99%